Fluorogenic Gold Nanoparticle (AuNP) Substrate A Model for the Controlled Release of Molecules from AuNP Nanocarriers via Interfacial Staudinger-Bertozzi Ligation - Luo, Wilson (Langmuir : the ACS journal of surfaces and colloids, 2017)
The ability to regulate small-molecule release from metallic nanoparticle substrates offers unprecedented opportunities for nanocarrier-based imaging, sensing, and drug-delivery applications. Herein we report a novel and highly specific release methodology off gold nanoparticle (AuNP) surfaces based on the bioorthogonal Staudinger-Bertozzi ligation. A thiol ligand bearing the molecular cargo, a Rhodamine B dye derivative, was synthesized and used to modify small water-soluble 5 nm AuNPs. Upon incorporation into the AuNP monolayer, we observed efficient quenching of the dye emission, resulting in a very low level of fluorescence emission that provided the baseline from which cargo release was monitored. We examined the ability of these AuNPs to react with azide molecules via Staudinger-Bertozzi ligation on the nanoparticle surface by monitoring the fluorescence emission after the introduction of an organic azide. We observed an immediate increase in emission intensity upon azide addition, which corresponded to the release of the dye into the bulk solution. The 31P NMR spectrum of the AuNP product also agrees with the formation of the ligation product. Thus this system represents a novel and highly specific release methodology off AuNP surfaces that can have potential applications in drug delivery, sensing, and materials science